The determinant of stock market via macroeconomic variable evidence from Malaysia / Nurul Syuhada Mohamad Nazir - Mohamad Nazir, Nurul Syuhada (2016)
This study explores the interaction between stock market return toward some key elements in macroeconomic variable which is interest rate and gross domestic product for the case in Malaysia. Apart from that, this study wants to know about the stock market return in Malaysia is a very sensitive or not toward the changes in the macroeconomic variables that have been chosen. Besides, in this study, it will explain to the cointegrating relationship between the variable in a long run relationship or not. Furthermore, in this study the main highlights that Malaysian stock market has any interaction with interest rate and gross domestic product.